Excavation Method of Rock Masses at the Matenggeng Dam, Indonesia - Afandi, Valentino Ilham; Indrawan, I Gde Budi; Husein, Salahuddin (Geological Engineering Department Universitas Gadjah Mada, 2025)
This paper presents the results of engineering geological investigations and determination of rock mass excavation methods in the main dam area of Matenggeng Dam. The study was carried out through engineering geological mapping, core drill evaluation and supported by laboratory test data. Classifications of rock masses were carried out based on the Geological Strength Index (GSI) and Rock Mass Rating (RMR) to analyze the excavation method. The results showed research area consisted of lithology in the form of andesite, intercalation sandstone - gravelly sandstone unit, intercalation sandstone - siltstone unit, and alluvium deposits. However, at the main dam area consists of lithology in the form of intercalation sandstone-siltstone unit and intercalation sandstone-gravelly sandstone unit. The rock masses at the main dam excavation line have a weathering degree from moderately to complately weathered. Intact rocks have Uniaxial Compressive Strength (UCS) values ranging from 1-50 Mpa and are a category of extremly weak to moderate rocks. The rock mass of intercalation sandstone-siltstone with very poor to poor quality (GSI (0 - 58), RMR (8 - 45)), and intercalation sandstone-gravelly sandstone with poor to fair quality (GSI (20 - 59), RMR (20 - 68)). The recommended rock excavation method based on the EXCASS System is diggir, easy ripper, and hard ripper.